فاعلية برنامج قائم على الاسترخاء العضلي لخفض أعراض ما بعد الصدمة النفسية لدى الأطفال الفلسطينيين - الحموز، عايد محمد عثمان; راشد، أنور أحمد عيسى (المركز القومي للبحوث غزة, 2019)
تناولت الدراسة فاعلية برنامج إرشادي قائم على تقنيات الاسترخاء العضلي في خفض أعراض ما بعد الصدمة النفسية الناتجة عن ممارسات الاحتلال الإسرائيلي ضد الأطفال الفلسطينيين، تمثلت مشكلة الدراسة في قلة وجود برامج إرشادية في فلسطين تسعى لخفض أعراض ما بعد الصدمة النفسية الناتجة عن ممارسات الاحتلال الإسرائيلي ضد الأطفال الفلسطينيين للحيلولة دون تحول هذه الأعراض لأمراض مزمنة تؤثر على سلوك الأطفال المستقبلي. نبعت أهمية الدراسة من تناولها لفئة ذات طبيعة خاصة وهم الأطفال الفلسطينيين الذين يعانون من اضطراب أعراض ما بعد الصدمة النفسية الناتجة عن ممارسات الاحتلال الإسرائيلي ضدهم، ومن أهمية البرنامج المستخدم والمتمثل في تقنيات الاسترخاء العضلي لما لهذه التقنيات من قدرة على علاج الكثير من الاضطرابات والمشكلات السلوكية. هدفت الدراسة التعرف إلى فاعلية برنامج إرشادي قائم على تقنيات الاسترخاء العضلي في خفض أعراض ما بعد الصدمة النفسية الناتجة عن ممارسات الاحتلال الإسرائيلي ضد الأطفال الفلسطينيين في محافظة الخليل، اتبعت الدراسة المنهج التجريبي والمنهج الوصفي التحليلي. أوضحت نتائج الدراسة وجود فروق على الدرجة الكلية وباقي الأبعاد الأخرى في متوسطات فاعلية برنامج إرشادي قائم على تقنيات الاسترخاء العضلي في علاج أعراض ما بعد الصدمة النفسية تعزى للطريقة (ضابطة/ تجريبية) لصالح أفراد المجموعة التجريبية. ووجود فروق تعزى للمدرسة (وكالة/ حكومة) لصالح مدرسة الحكومة. ووجود فروق تعزى للتفاعل بين (المجموعة/ المدرسة) لصالح مدرسة الحكومة من أفراد المجموعة التجريبية. خرجت الدراسة بعدد من التوصيات من أهمها الدعوة إلى العمل بالبرنامج المستخدم في هذه الدراسة وضرورة تطبيق أساليبه الإرشادية بين طلبة المدارس من قبل المرشدين بصورة دائمة. والاهتمام بإنشاء مؤسسات تهتم بعلاج الأطفال الذين يعانون من الصدمات النفسية وأعراض ما بعد الصدمة النفسية الناتجة عن ممارسات الاحتلال الإسرائيلي. كما اقترحت دراسة الاضطرابات النفس جسمية الناتجة عن ممارسة الاحتلال الإسرائيلي في المجتمع الفلسطيني وفاعلية تمارين الاسترخاء في خفضها.
This study investigated the effectiveness of counseling programme based on Muscular relaxation in decreasing Post Traumatic Stress Disorder (PTSD) that resulted from the practices of Israeli occupation against the Palestinian children. The problem of the study represented in the lack of counseling program in Palestine that attempt to decrease the (PTSD), which came as a result of the practices of Israeli occupation anainst the Palestinian children in order to prevent these syndromes to be developed into chronic disorders that impact children's future. The importance of this study comes from its focus on the studied category which is significant; this category embraced children suffering from (PTSD) that appeared due to practices of Israeli occupation. The study is also important due to the significance of the program used as being based on the muscular relaxation techniques; such programme proved efficiency in resolving an array of psychological disorders and problems. The study aimed at assessing the effectiveness of counseling program based on Muscular relaxation in decreasing (PTSD) that resulted from the practices of Israeli occupation against the Palestinian children at Hebron district. The study followed the experimental and the analytical descriptive approach. The results of the study turned out differences on the total score and the rest of the other dimensions in the averages based on the effectiveness of muscle relaxation techniques in the treatment of the symptoms of post-trauma due to the way (stander / experimental) in favor of the experimental group. And the existence of differences due to the school (agency / government) in favor of the government school and the existence of differences that are due to the interaction between (group / school) in favor of government school from experimental group. In the light of these findings the study made several recommendations the most important of these were; adopting this counseling program then applying it on the students of schools on regular basis. More attention is to be paid to establishing of institutions that concerned with the treatment of children who suffer from (PTSD) resulting from the Israeli occupation practices. also I suggested to study the Physical self-unrests resulting from the Israeli occupation practices in the Palestinian society and the effectiveness of relaxation exercises in reduction these unrests.
Keywords: الأطفال الفلسطينيين -- الاحتلال الإسرائيلى -- الصدمات النفسية -- أعراض ما بعد الصدمة النفسية -- الاسترخاء العضلي -- الإرشاد النفسى -- البرامج الإرشادية